The burgeoning recognition and accommodation of the social supply of drugs in international criminal justice systems: An eleven-nation comparative overview - Coomber, R.; Moyle, L.; Belackova, V.; Decorte, T.; Hakkarainen, P.; Hathaway, A.; Laidler, K.; Lenton, Simon; Murphy, S.; Scott, J.; Stefunkova, M.; van de Ven, K.; et al. (Elsevier BV, 2018)
© 2018 Background: It is now commonly accepted that there exists a form of drug supply, that involves the non-commercial supply of drugs to friends and acquaintances for little or no profit, which is qualitatively different from profit motivated ‘drug dealing proper’. ‘Social supply’ as it has become known, has a strong conceptual footprint in the United Kingdom, shaped by empirical research, policy discussion and its accommodation in legal frameworks. Though scholarship has emerged in a number of contexts outside the UK, the extent to which social supply has developed as an internationally recognised concept in criminal justice contexts is still unclear. Methods: Drawing on an established international social supply research network across eleven nations, this paper provides the first assessment of social supply as an internationally relevant concept. Data derives from individual and team research stemming from Australia, Belgium, Canada, Czech Republic, Finland, Germany, Hong Kong, the Netherlands, England and Wales, and the United States, supported by expert reflection on research evidence and analysis of sentencing and media reporting in each context. In situ social supply experts addressed a common set of questions regarding the nature of social supply for their particular context including: an overview of social supply research activity, reflection on the extent that differentiation is accommodated in drug supply sentencing frameworks; evaluating the extent to which social supply is recognised in legal discourse and in sentencing practices and more broadly by e.g. criminal justice professionals in the public sphere. A thematic analysis of these scripts was undertaken and emergent themes were developed. Whilst having an absence of local research, New Zealand is also included in the analysis as there exists a genuine discursive presence of social supply in the drug control and sentencing policy contexts in that country. Results: Findings suggest that while social supply has been found to exist as a real and distinct behaviour, its acceptance and application in criminal justice systems ranges from explicit through to implicit. In the absence of dedicated guiding frameworks, strong use is made of discretion and mitigating circumstances in attempts to acknowledge supply differentiation. In some jurisdictions, there is no accommodation of social supply, and while aggravating factors can be applied to differentiate more serious offences, social suppliers remain subject to arbitrary deterrent sentencing apparatus. Conclusion: Due to the shifting sands of politics, mood, or geographical disparity, reliance on judicial discretion and the use of mitigating circumstances to implement commensurate sentences for social suppliers is no longer sufficient. Further research is required to strengthen the con ceptual presence of social supply in policy and practice as a behaviour that extends beyond cannabis and is relevant to users of all drugs. Research informed guidelines and/or specific sentencing provisions for social suppliers would provide fewer possibilities for inconsistency and promote more proportionate outcomes for this fast-growing group.